Production of Assistance Brake for Mechanical Wheelchair - Sedlak, Josef; Vanek, Roman; Chladil, Josef (Manufacturing Technology Journal, 2018)
The paper deals with the proposal for the production of an assistance brake for a mechanical wheelchair, which will help the wheelchair users to move in the course of overcoming barrier-free and partially barrier obstacles. The introductory part of the contribution characterizes the basic requirements of the brake for a mechanical wheelchair, especially from a legal point of view and in terms of their safety. The practical part of the paper deals with the production of a prototype pair of assistance brakes in school conditions (workshop C2 of the Institute of Mechanical Engineering, Faculty of Mechanical Engineering, Brno University of Technology) using conventional machining technology (brake body production) and 3D printing technology (braking segment production). Part of the practical part also requires testing in typical / real wheelchair conditions. The contribution is completed by the technical and economic evaluation of the prototype pair of assistance brakes, which is related to the calculation of the total cost of their production.
Keywords: Emergency Brake; Mechanical Wheelchair; Braking segment; Wheelchair Access; Wheelchairs